Roles And Responsibilities Investigator In Investigation of Illegal Mining In Society Mining for Environmental Sustainability - Kurniawan Daeli; Rakhmat Bowo Suharto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
The problem in this research are: setting illegal mining in the legislation and the role of the investigator in the investigation of a case of illegal mining. Based on the results of the study concluded that: setting illegal mining in the legislation is in terms of penal policy within the meaning of penal law enforcement policy includes several stages, including the stage of formulation, application phase and the execution phase, but in relation to this, the discussion will be focused on the application phase for the implementation of Act No. 4 of 2009 on the eradication of illegal mining, which happened recently. The role of the investigator in the investigation of illegal mining case is Supervisors investigators have experience and knowledge are qualified when she served so supervisory investigator. In addition, the supervisory investigator is also expected to continue to follow the development of crime which took place at the time. Thus, the supervisory investigator will not be lacking in the process of analyzing the monitored object. Supervisory investigator to conduct surveillance should be independent and not affected by the intervention whatsoever. The conclusion of this study is the context of law enforcement against Act No. 4 of 2009 has experienced a bottleneck, so that its application does not reflect a sense of justice for the perpetrators of violations in the field of illegal mining. Supervision of the investigation basically already done well with the basic rules Police chief Regulation No. 12 of 2009, but for the disciplinary action is not implemented.Keywords: Roles, Responsibilities, Investigator, Investigation, Illegal Mining, Mining